Weather-resistant polyurethane and preparation method thereof

By constructing a synergistic weather resistance mechanism involving ultraviolet absorption, free radical capture, and physical shielding, the problem of performance degradation of polyurethane coatings in outdoor environments has been solved, achieving high-performance improvement in weather resistance and corrosion resistance.

CN121293859APending Publication Date: 2026-01-09TAICANG DEDE NEW MATERIALS TECHNOLOGY CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202511500160.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-21
Publication Date
2026-01-09

AI Technical Summary

Technical Problem

Existing polyurethane coatings are susceptible to corrosion from ultraviolet light and salt spray when exposed to the outdoors for a long time, resulting in performance degradation and failing to meet the weather resistance and corrosion resistance requirements of high-performance coatings in fields such as construction and transportation.

Method used

A synergistic weather resistance mechanism is constructed by using benzotriazole UV absorbers, light-hindered amine stabilizers, rutile titanium dioxide, nano zinc oxide, and wet-process sericite powder to form a chemical protective layer and physical shielding, thereby enhancing the coating's UV absorption, free radical capture, and structural density.

Benefits of technology

It significantly improves the weather resistance and corrosion resistance of the coating, reduces chalking level, decreases discoloration and gloss loss, controls the spread width of scribing corrosion within a reasonable range, and maintains excellent mechanical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention belongs to the technical field of preparation and surface protection of polyurethane coatings, and particularly relates to weather-resistant polyurethane and a preparation method thereof. The coating provided by the invention is composed of a component A and a component B according to a weight ratio of 1: (0.2-0.4). The component A is prepared from water-based fluorine-containing hydroxy acrylic dispersion resin with a high hydroxyl value, GMA (glycidyl methacrylate) grafted modified water-based acrylic dispersion resin, a benzotriazole ultraviolet light absorber, a light hindered amine stabilizer, rutile titanium dioxide, wet sericite powder, nano zinc oxide and auxiliaries; and the component B comprises an aliphatic isocyanate curing agent and propylene glycol diacetate. By constructing a quadruple synergistic weather-resistant mechanism of ultraviolet absorption, free radical capture, physical shielding and structural densification, the weather resistance and corrosion resistance of the coating are remarkably improved while the coating keeps excellent adhesive force (0-1 level) and hardness (2H-3H), the color change delta E is smaller than or equal to 1.8 after artificial accelerated aging for 1000 hours, the gloss loss rate is smaller than or equal to 23%, and the weather resistance and corrosion resistance of the coating are greatly improved. And the corrosion spreading width of a 600-hour salt spray test lineation is less than or equal to 2.3 mm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of polyurethane coating preparation and surface protection technology, specifically relating to a weather-resistant polyurethane and its preparation method. Background Technology

[0002] Polyurethane coatings, due to their excellent substrate adhesion, mechanical strength, and application adaptability, are widely used in building exterior wall decoration, transportation vehicle surface protection, and industrial equipment and steel structure corrosion protection, becoming an indispensable category in modern coating systems. Existing conventional polyurethane coatings, through the cross-linking reaction of the resin matrix and curing agent, can form a coating structure that meets the basic usage requirements and maintains good performance stability indoors or in mild environments, thus maintaining a significant market share for a long time.

[0003] However, when polyurethane coatings are applied to outdoor environments with long-term exposure, their performance is easily degraded by complex environmental factors, a problem that has become a key bottleneck restricting their further expansion. Ultraviolet light (especially the UVB band) in outdoor environments is the core cause of coating aging. UV energy can damage the chemical structure of polyurethane molecular chains, triggering reactions such as chain breakage and decreased cross-linking density. This ultimately manifests as chalking, color change (increased ΔE value), and gloss loss (increased gloss rate). In severe cases, it can lead to coating cracking and peeling, resulting in the loss of both protective and decorative functions. Accelerated aging tests conducted according to the GB / T1865 standard show that ordinary polyurethane coatings generally exhibit chalking, color change, and gloss loss after 1000 hours of testing. Typically, the chalking level exceeds level 2, the color change ΔE > 3.0, and the gloss loss rate > 30%, making it difficult to meet the current durability upgrade requirements for long-term color retention, gloss retention, and chalking resistance in outdoor construction, transportation equipment, and other scenarios.

[0004] Meanwhile, in environments with salt spray corrosion, such as coastal areas and industrial zones, the corrosion resistance of polyurethane coatings is significantly insufficient. Corrosive media such as chloride ions in salt spray can easily penetrate the coating and react with the substrate, leading to blistering and rusting of the coating. The width of scratch-line corrosion often exceeds 3.0 mm (tested according to GB / T1771 standard). The root cause of this problem is that the coating cannot form an absolute impermeability barrier, failing to completely prevent the intrusion of water, oxygen, and corrosive media, thus leading to substrate corrosion and coating failure.

[0005] To address these performance shortcomings, the industry has undertaken some improvement attempts, such as adding UV absorbers to coatings to mitigate UV aging and adding fillers like titanium dioxide to enhance physical shielding. However, these improvement schemes still have several limitations. On the one hand, adding large amounts of functional components can easily disrupt the balance of the coating system. For example, excessive UV absorbers can lead to reduced coating adhesion, and excessive addition of titanium dioxide can also cause a decrease in coating hardness and impaired density, thus weakening the overall shielding effect. On the other hand, in existing solutions, UV aging protection and salt spray corrosion protection are often independent and lack systematic synergistic consideration, making it difficult for the coating to simultaneously improve both weather resistance and corrosion resistance while maintaining basic mechanical properties. Summary of the Invention

[0006] To address the shortcomings of existing technologies, this invention provides a weather-resistant polyurethane and its preparation method. The purpose of this invention is to develop a novel polyurethane coating that, while maintaining basic mechanical properties, effectively addresses the challenges of harsh environments such as outdoor UV aging and salt spray corrosion, significantly improving long-term weather resistance and corrosion resistance, thereby better meeting the application needs of high-performance coatings in fields such as construction, transportation, and industrial corrosion protection.

[0007] The first aspect of the present invention is to provide a weather-resistant polyurethane coating, which is composed of component A and component B in a weight ratio of 1:(0.2-0.4); Component A comprises the following raw materials in parts by weight: 1.0 part of water-based fluorinated high-hydroxyl-value acrylic acid dispersion resin; 0.8-1.0 parts of GMA-grafted modified waterborne acrylic dispersion resin; 0.03-0.05 parts of benzotriazole ultraviolet absorber; 0.03-0.05 parts of light-hindered amine stabilizer; 0.3-0.5 parts of rutile titanium dioxide; 0.2-0.4 parts of wet-processed sericite powder; Nano zinc oxide 0.05-0.1 parts; Dispersant 0.02-0.03 parts; 0.01-0.02 parts of defoamer; Leveling agent 0.01-0.02 parts; Thickener 0.01-0.02 parts; 0.3-0.6 parts deionized water; Component B comprises the following raw materials in parts by weight: 1.0 part of aliphatic isocyanate curing agent; 0.2-0.3 parts of propylene glycol diacetate.

[0008] As a further optimization of weather-resistant polyurethane coatings, the weight of GMA grafted modified waterborne acrylic dispersion resin is 0.85-0.95 parts.

[0009] As a further optimization of weather-resistant polyurethane coatings, the benzotriazole UV absorber is Tinuvin 1130, and the light-hindered amine stabilizer is Tinuvin 292.

[0010] As a further optimization of weather-resistant polyurethane coatings, the weight parts of rutile titanium dioxide are 0.4-0.45 parts, the weight parts of wet-process sericite powder are 0.3-0.35 parts, and the weight parts of nano zinc oxide are 0.075-0.08 parts.

[0011] As a further optimization of weather-resistant polyurethane coatings, the weight ratio of benzotriazole UV absorber to light-hindered amine stabilizer is 1:(0.8-1.2).

[0012] As a further optimization of weather-resistant polyurethane coatings, the weight ratio of nano zinc oxide to rutile titanium dioxide is (0.15-0.25):1.

[0013] A second aspect of this invention is to provide a method for preparing a weather-resistant polyurethane coating, comprising the following steps: Preparation of component A: S1: Add dispersant and defoamer to deionized water in sequence under high-speed stirring, and stir until completely dissolved; S2: Keep stirring at high speed, and add benzotriazole UV absorber, light-hindered amine stabilizer, rutile titanium dioxide, wet sericite powder and nano zinc oxide in sequence. Continue stirring at high speed after adding the materials to form a uniform slurry. S3: Grind the slurry to a fineness of ≤50μm, and then stir at low speed to eliminate air bubbles; S4: While maintaining low-speed stirring, add water-based fluorinated high-hydroxyl-value acrylic dispersion resin and GMA grafted modified water-based acrylic dispersion resin in sequence. After stirring, add leveling agent and thickener, adjust the speed and stir until the system is uniform, and filter to obtain component A. Preparation of component B: Under stirring, propylene glycol diacetate is slowly added to the aliphatic isocyanate curing agent and stirred continuously until homogeneous and without stratification to obtain component B.

[0014] As a further optimization of the preparation method of weather-resistant polyurethane coating, in steps S1 and S2, the high-speed stirring speed is 1000-1500 r / min; in step S2, the high-speed stirring duration is 15-20 min; in step S3, the low-speed stirring speed is 400-600 r / min, and the duration is 8-12 min; in step S4, after adding the resin, the low-speed stirring speed is 400-600 r / min, and after adding the leveling agent and thickener, the speed is adjusted to 600-1000 r / min and stirred for 8-10 min until the system viscosity reaches the 25-30s of the Forecast-4 cup.

[0015] As a further optimization of the preparation method of weather-resistant polyurethane coating, in the preparation of component B, the stirring speed is 700-900 r / min, and stirring is continued for 8-10 min after adding propylene glycol diacetate.

[0016] As a further optimization of the preparation method of weather-resistant polyurethane coating, according to the weight ratio A:B=1:(0.2-0.4), component B is slowly added to component A, and the mixture is stirred at a low speed of 500-700 r / min for 4-6 min to obtain a weather-resistant polyurethane coating that can be used for coating.

[0017] Beneficial effects Compared with existing technologies, this invention significantly improves the overall performance of polyurethane coatings by constructing a four-pronged synergistic weather resistance mechanism involving ultraviolet absorption, free radical capture, physical shielding, and structural densification. Specifically, benzotriazole ultraviolet absorbers and light-hindered amine stabilizers together form a chemical protective layer, effectively absorbing ultraviolet light and blocking free radical chain reactions; rutile titanium dioxide and nano-zinc oxide form a physical shield, blocking ultraviolet penetration; and wet-process sericite powder enhances coating density through filling and layered structure, constructing an anti-permeability barrier. Test results show that, while maintaining excellent adhesion (up to grade 0) and hardness (up to 3H), the coating exhibits a chalking grade of no more than grade 2, discoloration ΔE ≤ 1.8, and gloss loss rate ≤ 23% after 1000 hours of accelerated aging. Furthermore, in a 600-hour salt spray test, the scratch corrosion spread width is ≤ 2.3 mm, with no blistering or rusting, effectively addressing the problems of insufficient long-term weather resistance and limited corrosion protection performance of traditional polyurethane coatings. Detailed Implementation

[0018] The present invention is further illustrated below with specific embodiments. These embodiments are exemplary and intended to illustrate the problem and explain the present invention, and are not intended to be limiting.

[0019] Example 1 The weather-resistant polyurethane in this embodiment includes component A and component B, with a weight ratio of 1:0.3 between components A and B.

[0020] Component A includes: Waterborne fluorinated high hydroxyl value hydroxyl acrylic acid dispersion resin (Shiquanxing 2233F): 1.0 parts by weight; GMA grafted modified waterborne acrylic dispersion resin (Shiquanxing 5136): 0.9 parts by weight; Benzotriazole UV absorber (Tinuvin 1130): 0.04 parts by weight; Light-hindered amine stabilizer (Tinuvin 292): 0.04 parts by weight; Rutile titanium dioxide CR828: 0.4 parts by weight; Wet-processed sericite powder (Chuzhou Gerui): 0.3 parts by weight; Nano zinc oxide (particle size 20-50nm): 0.075 parts by weight; Dispersant (BYK-183): 0.025 parts by weight; Defoamer (BYK-093): 0.015 parts by weight; Leveling agent (TEGO-450): 0.015 parts by weight; Thickener (BYK-420): 0.015 parts by weight; Deionized water: 0.45 parts by weight.

[0021] Component B includes: Aliphatic isocyanate curing agent (Bayhydur XP 2655): 1.0 part by weight; Propylene glycol diacetate (PGDA): 0.25 parts by weight.

[0022] The preparation method of component A includes the following steps: Step S1: Add deionized water to a stainless steel mixing tank, turn on high-speed stirring (1200 r / min), add BYK-183 dispersant and BYK-093 defoamer in sequence, and continue stirring for 5 minutes until completely dissolved.

[0023] Step S2: Keep the rotation speed at 1200 r / min, and add Tinuvin 1130, Tinuvin 292, CR828 titanium dioxide, wet sericite powder and nano zinc oxide in sequence (1 min apart for each). After adding the materials, stir at high speed for 18 min to form a uniform grayish-white slurry.

[0024] Step S3: Transfer the slurry to a sand mill and grind it to a fineness of ≤50μm. After returning it to the mixing tank, switch to low-speed stirring (500 r / min) for 10 minutes to eliminate air bubbles.

[0025] Step S4: While stirring at 500 r / min, add Shiquanxing 2233F resin and Shiquanxing 5136 resin in sequence. After stirring for 5 min, add TEGO-450 leveling agent and BYK-420 thickener. Adjust the speed to 800 r / min and stir for 9 min until the system is homogeneous (Ford-4 cup viscosity 28s, 25℃). Finally, filter through a 100-mesh filter to obtain component A.

[0026] The preparation method of component B includes the following steps: add Bayhydur XP 2655 curing agent to a clean plastic mixing tank, start medium-speed stirring (800 r / min), slowly add PGDA film-forming aid (addition time 2 min), and continue stirring for 9 min until uniform and without stratification to obtain component B.

[0027] The preparation of weather-resistant polyurethane coating includes the following steps: according to the weight ratio of A:B=1:0.3, slowly add component B to component A, turn on low speed stirring (600 r / min) for 5 minutes to mix evenly, and obtain a coating that meets the conditions for spraying construction.

[0028] Examples 2-4 The composition and dosage of components A and B in Examples 2-4 are shown in Tables 1 and 2. The preparation methods of components A, B, and weather-resistant polyurethane coatings are the same as those in Example 1.

[0029] Table 1. Composition and dosage of component A in each embodiment Table 2 Composition and dosage of component B in each embodiment Comparative Example 1 Based on the scheme of Example 1, the only difference from Example 1 is that benzotriazole UV absorber (Tinuvin 1130) is not added to component A.

[0030] Comparative Example 2 Based on the scheme of Example 1, the only difference from Example 1 is that no light-hindered amine stabilizer (Tinuvin 292) is added to component A.

[0031] Comparative Example 3 Based on the scheme of Example 1, the only difference from Example 1 is that nano zinc oxide is not added to component A, and the amount of rutile titanium dioxide CR828 is reduced to 0.1 parts (which only provides basic coverage and cannot effectively block ultraviolet rays).

[0032] Comparative Example 4 Based on the scheme of Example 1, the only difference from Example 1 is that wet-processed sericite powder is not added to component A at all.

[0033] Comparative Example 5 Based on the scheme of Example 1, the only difference from Example 1 is that Tinuvin 1130 (UV absorber) and Tinuvin 292 (light stabilizer) are not added to component A at the same time.

[0034] Test Example 1 Mechanical performance tests were conducted according to the adhesion standard GB / T 9286 and the hardness standard GB / T 6739. Weather-resistant polyurethane coating specimens prepared in each example (1-4) and comparative example (1-5) were used. The adhesion grade of the specimens was determined by the cross-cut test, and the pencil hardness value of the specimens was determined by the pencil hardness test. The initial adhesion and pencil hardness data of each sample were directly obtained. The test results are shown in Table 3.

[0035] Table 3 Mechanical Performance Test Results Test Example 2 Artificial accelerated aging experiments were conducted according to GB / T 1865 standard. First, the weather-resistant polyurethane coatings of each example (1-4) and comparative example (1-5) were coated on the substrate to make specimens according to the spraying construction conditions. Then, all specimens were placed in an ultraviolet aging test chamber and the test conditions were set as follows: UVB-313 lamp, 60℃ ultraviolet light irradiation for 4h / 50℃ condensation for 4h cycle. The specimens were taken out every 250 hours to evaluate the chalking grade, discoloration degree (ΔE) and gloss loss rate. The test was continued until 1000 hours and the final data were recorded. The test results are shown in Table 4.

[0036] Table 4 Results of Artificial Accelerated Aging Experiments Test Example 3 The neutral salt spray resistance test was conducted according to GB / T 1771 standard. First, steel plate specimens coated with weather-resistant polyurethane coatings for each example (1-4) and comparative example (1-5) were prepared, and a single line was made on each specimen. Then, the specimens were placed in a salt spray chamber and continuously sprayed with 5% NaCl solution (chamber temperature 35℃). The specimens were observed every 120 hours, and the corrosion spread width (mm) at the line and whether blistering or rusting occurred in the area outside the line were recorded. After 600 hours of testing, the data were compiled, and the test results are shown in Table 5.

[0037] Table 5 Results of Neutral Salt Spray Test Results and Analysis As shown in Table 3, the weather-resistant polyurethane coatings prepared in Examples 1-4 exhibit excellent mechanical properties, with adhesion grades all reaching level 1 or higher, and adhesion grades of Examples 2 and 4 reaching level 0. Pencil hardness was consistently 2H or higher, with Example 2 reaching a maximum pencil hardness of 3H. This indicates that the coating system can form a coating structure with strong adhesion and high hardness, meeting the mechanical strength requirements for basic applications. The adhesion grades and pencil hardness of Comparative Examples 1-5 are basically the same as those of the Examples, indicating that the coating system's ability to form a coating structure with strong adhesion and high hardness is mainly attributed to the coating's base components. Components related to ultraviolet absorption, free radical capture, physical shielding, or structural densification mechanisms have no significant impact on the mechanical adhesion and hardness formed during the initial curing of the coating, also demonstrating the stability of the coating's base formulation.

[0038] As shown in Table 4, Examples 1-4 all exhibited excellent weather resistance in the 1000h accelerated aging test: the chalking grade was controlled at or below level 2, with Example 2 showing the best performance, reaching level 0; the discoloration degree ΔE was less than 1.8, with Examples 2 and 4 at only 1.0 and 1.1 respectively; the gloss loss rate was less than 23%, with Example 2 being the lowest at only 12%. This fully demonstrates that the coating system constructed in this invention can effectively resist UV-induced coating degradation and maintain the long-term stability of the coating's appearance and performance. The aging performance of the comparative examples was comprehensively inferior to that of the examples, further verifying the synergistic necessity of each weather-resistant component. Comparative Example 1, due to the lack of UV absorber (Tinuvin 1130), saw its chalking grade rise to level 2, ΔE reach 3.2, and gloss loss rate as high as 35%, indicating that direct exposure of the resin to UV light led to accelerated molecular chain breakage; Comparative Example 2, due to the lack of light stabilizer (Tinuvin 1130), showed a different performance. Example 292 shows that ΔE increased to 2.6 and gloss loss rate reached 28%, indicating that the free radical chain reaction was not effectively suppressed. Comparative Example 3, due to the lack of nano zinc oxide and insufficient titanium dioxide, had a weakened physical shielding effect, resulting in a chalking grade of 3, ΔE of 4.2, and gloss loss rate of 45%, indicating that ultraviolet rays could penetrate the coating more easily, causing overall aging. Comparative Example 4, without the addition of wet-process sericite powder, had a chalking grade of 2, ΔE of 2.0, and gloss loss rate of 22%, which was inferior to the example but slightly better than the other comparative examples, indicating that even if the chemical weathering mechanism was maintained, the lack of structural density would weaken the overall weather resistance of the coating. Comparative Example 5, due to the simultaneous lack of ultraviolet absorbers and light stabilizers, had a chalking grade as high as 4, ΔE of 5.3, and gloss loss rate as high as 60%, indicating that in the absence of a dual chemical protection mechanism, the coating aging rate increased sharply, further demonstrating the importance of constructing a synergistic weathering mechanism.

[0039] As shown in Table 5, Examples 1-4 exhibited excellent corrosion resistance in the 600-hour neutral salt spray test, with the width of the scratched corrosion spread controlled within 2.3 mm. Examples 2 and 4 showed spread widths of only 1.5 mm and 1.6 mm, respectively. No blistering or rust was observed outside the scratches in all examples, indicating good coating density and effective protection against salt spray penetration. The corrosion resistance of the comparative examples was weaker than that of the examples. Comparative Example 4, lacking any wet-process sericite powder and thus lacking a structural densification mechanism, not only showed a scratched corrosion spread width of 4.2 mm but also significant blistering near the scratches, demonstrating that the labyrinthine barrier formed by sericite effectively prevents the penetration of water, oxygen, and salt. While Comparative Examples 1-3 and 5 showed no blistering or rust, their scratched corrosion spread widths exceeded 2.8 mm, indicating that the lack of a synergistic weathering mechanism weakened the overall protective properties of the coating.

[0040] The test results in Tables 3-5 show that the weather-resistant polyurethane coating of this invention achieves significant weather resistance and corrosion resistance while maintaining excellent mechanical properties. This performance improvement stems from the synergistic system of four weather-resistant components: UV absorption, free radical capture, physical shielding, and structural densification. Specifically, the benzotriazole UV absorber (Tinuvin 1130) absorbs UV light through a preventative mechanism, avoiding direct damage to the resin molecular chains; the photohindered amine stabilizer (Tinuvin 292) removes free radicals generated by photoaging through an interception mechanism, blocking the chain oxidation reaction; rutile titanium dioxide and nano-zinc oxide form a physical shield, further preventing UV penetration of the coating; and wet-process sericite powder, through structural densification, constructs an anti-permeability barrier, reducing the intrusion of corrosive media. The test data of the comparative examples further corroborate this synergistic effect. The absence of any single mechanism leads to a decrease in weather resistance or corrosion resistance, while Comparative Example 5, lacking both chemical mechanisms, shows the most severe performance degradation. In summary, the coating system of this invention comprehensively improves the weather resistance, mechanical properties, and corrosion resistance of the coating through a four-fold synergistic weather resistance mechanism of ultraviolet absorption, free radical capture, physical shielding, and structural densification, thus solving the problem of insufficient long-term weather resistance of traditional polyurethane coatings.

[0041] The above embodiments are exemplary and are intended to illustrate the technical concept and features of the present invention, so that those skilled in the art can understand the content of the present invention and implement it accordingly. They should not be construed as limiting the scope of protection of the present invention. All equivalent changes or modifications made according to the spirit and essence of the present invention should be covered within the scope of protection of the present invention.

Claims

1. A weather-resistant polyurethane coating, characterized in that, It consists of component A and component B in a weight ratio of 1:(0.2-0.4); Component A comprises the following raw materials in parts by weight: 1.0 part of water-based fluorinated high-hydroxyl-value acrylic acid dispersion resin; 0.8-1.0 parts of GMA-grafted modified waterborne acrylic dispersion resin; 0.03-0.05 parts of benzotriazole ultraviolet absorber; 0.03-0.05 parts of light-hindered amine stabilizer; 0.3-0.5 parts of rutile titanium dioxide; 0.2-0.4 parts of wet-processed sericite powder; Nano zinc oxide 0.05-0.1 parts; Dispersant 0.02-0.03 parts; 0.01-0.02 parts of defoamer; Leveling agent 0.01-0.02 parts; Thickener 0.01-0.02 parts; 0.3-0.6 parts deionized water; Component B comprises the following raw materials in parts by weight: 1.0 part of aliphatic isocyanate curing agent; 0.2-0.3 parts of propylene glycol diacetate.

2. The weather-resistant polyurethane coating according to claim 1, characterized in that, The GMA-grafted modified waterborne acrylic dispersion resin has a weight ratio of 0.85-0.95 parts.

3. The weather-resistant polyurethane coating according to claim 1, characterized in that, The benzotriazole UV absorber is Tinuvin 1130, and the light-hindered amine stabilizer is Tinuvin 292.

4. The weather-resistant polyurethane coating according to claim 1, characterized in that, The rutile titanium dioxide comprises 0.4-0.45 parts by weight, the wet-process sericite powder comprises 0.3-0.35 parts by weight, and the nano zinc oxide comprises 0.075-0.08 parts by weight.

5. The weather-resistant polyurethane coating according to claim 1, characterized in that, The weight ratio of the benzotriazole ultraviolet absorber to the photohindered amine stabilizer is 1:(0.8-1.2).

6. The weather-resistant polyurethane coating according to claim 1, characterized in that, The weight ratio of the nano zinc oxide to the rutile titanium dioxide is (0.15-0.25):

1.

7. A method for preparing a weather-resistant polyurethane coating as described in any one of claims 1-6, characterized in that, Includes the following steps: Preparation of component A: S1: Add dispersant and defoamer to deionized water in sequence under high-speed stirring, and stir until completely dissolved; S2: Keep stirring at high speed, and add benzotriazole UV absorber, light-hindered amine stabilizer, rutile titanium dioxide, wet sericite powder and nano zinc oxide in sequence. Continue stirring at high speed after adding the materials to form a uniform slurry. S3: Grind the slurry to a fineness of ≤50μm, and then stir at low speed to eliminate air bubbles; S4: While maintaining low-speed stirring, add water-based fluorinated high-hydroxyl-value acrylic dispersion resin and GMA grafted modified water-based acrylic dispersion resin in sequence. After stirring, add leveling agent and thickener, adjust the speed and stir until the system is uniform, and filter to obtain component A. Preparation of component B: Under stirring, propylene glycol diacetate is slowly added to the aliphatic isocyanate curing agent and stirred continuously until homogeneous and without stratification to obtain component B.

8. The preparation method according to claim 7, characterized in that, In steps S1 and S2, the high-speed stirring speed is 1000-1500 r / min; in step S2, the high-speed stirring duration is 15-20 min; in step S3, the low-speed stirring speed is 400-600 r / min, and the duration is 8-12 min. In step S4, after adding the resin, the low-speed stirring speed is 400-600 r / min. After adding the leveling agent and thickener, the speed is adjusted to 600-1000 r / min and stirred for 8-10 minutes until the system viscosity reaches the 25-30s of Fore-4 cup.

9. The preparation method according to claim 7, characterized in that, In the preparation of component B, the stirring speed is 700-900 r / min, and stirring is continued for 8-10 min after the addition of propylene glycol diacetate.

10. The preparation method according to claim 7, characterized in that, Mix component B slowly into component A by weight ratio A:B=1:(0.2-0.4), and stir at a low speed of 500-700 r / min until homogeneous. The stirring time is 4-6 min, and the resulting weather-resistant polyurethane coating can be used for coating.

Citation Information

Cited By

  • Weather-resistant powder coating for doors and windows and preparation method of weather-resistant powder coating

    CN121895837A

  • A weather-resistant powder coating for doors and windows and its preparation method

    CN121895837B